(3x^2-x):2+(2x^2-x):6=x
Решите как уравнение

полина2125 полина2125    2   24.04.2020 12:13    1

Ответы
KEK22813371488 KEK22813371488  13.10.2020 19:54

Объяснение:

\frac{(3 {x}^{2} - x)}{2} + \frac{(2 {x}^{2} - x) }{6} = x

\frac{3(3 {x}^{2} - x) + 2 {x}^{2} - x }{6} = x

\frac{9 {x}^{2} - 3x + 2 {x}^{2} - x}{6} = x

\frac{11 {x}^{2} - 4x }{6} = \frac{x}{1}

11х² - 4х = 6х

11х² - 4х - 6х = 0

11х² - 10х = 0

х (11х - 10) = 0

х = 0 или 11х - 10 = 0

11х = 10

х = 10 : 11

ответ: х = 0; 10/11

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра